PENGEMBANGAN BUKU PENDAMPING BERBASIS BUDAYA LOKAL BANJAR UNTUK MENINGKATKAN SIKAP PEDULI SOSIAL SISWA SEKOLAH DASAR - Normalasarie, - (2023)
ABSTRACT Normalasarie (2023). Development of a Companion Book Based on Local Banjar Culture to Improve the Social Attitudes of Elementary School Students. Social care is an action with a feeling of always wanting to help others in need which is manifested in attitudes or actions of sharing with others in need. The purpose of this study was to develop a companion book based on the local Banjar culture to increase social care for elementary school students. The development model used is ADDIE namely Analysis, Design, Development, Implementation, and Evaluation. Data Collection of this study is using observation, interviews, questionnaires, and documentation. The validation of the companion book involves educational experts and practitioners consisting of school principals, teachers and school supervisors. The companion book questionnaire involves the assessment of media experts, cultural experts, thematic experts, teacher and student responses to determine the effectiveness of the companion book in social care attitudes. The test subjects were limited to Mandikapau Barat 2 Elementary School, Banjarmasin, while the wide trial was conducted at Teluk Tiram 2 Elementary School, Banjarmasin and Antasan Kecil 1 Elementary School, Banjarmasin. This research was conducted because of the importance of increasing students' understanding of local Banjar culture and also the importance of developing students' sense of social care from an early age. Research on the development of companion books was carried out by incorporating material related to local Banjar culture and social values that could increase students' social awareness. The results of this study indicate that the companion book developed succeeded in increasing students' understanding of the local Banjar culture and also succeeded in increasing students' sense of social care. This can be seen from the increase in the pretest value before the application of the companion book, namely 23.33% in the complete category and after the implementation of the companion book is in the complete category, 100% is in the complete category. This is reinforced by statistical data describing an average pretest of 61.33% and posttest data of 92.88%. Thus it can be concluded that the development of a companion book based on local Banjar culture can be an effective alternative in increasing students' understanding of local Banjar culture and increasing students' sense of social care. Therefore it is suggested for related parties to consider local culture-based companion books in the elementary school curriculum. Keyword: Buku Pendamping, Banjar Local Culture, Social Care